T-lymphopoiesis is Severely Compromised in Ubiquitin-Green Fluorescent Protein Transgenic Mice - Faltusová, K; Báječný, M; Heizer, T; Páral, P; Nečas, E (Folia biologica, 2020)
Tagging cells of experimental organisms with genetic markers is commonly used in biomedical research. Insertion of artificial gene constructs can be highly beneficial for research as long as this tagging is functionally neutral and does not alter the tissue function. The transgenic UBC-GFP mouse has been recently found to be questionable in this respect, due to a latent stem cell defect compromising its lymphopoiesis and significantly influencing the results of competitive transplantation assays. In this study, we show that the stem cell defect present in UBC-GFP mice negatively affects T-lymphopoiesis significantly more than B-lymphopoiesis. The production of granulocytes is not negatively affected. The defect in T-lymphopoiesis causes a low total number of white blood cells in the peripheral blood of UBC-GFP mice which, together with the lower lymphoid/myeloid ratio in nucleated blood cells, is the only abnormal phenotype in untreated UBCGFP mice to have been found to date. The defective lymphopoiesis in UBC-GFP mice can be repaired by transplantation of congenic wild-type bone marrow cells, which then compensate for the insufficient production of T cells. Interestingly, the wild-type branch of haematopoiesis in chimaeric UBC-GFP/wild-type mice was more active in lymphopoiesis, and particularly towards production of T cells, compared to the lymphopoiesis in normal wild-type donors.
Keywords: lymfopoéza; myši; Mice, Transgenic; T-lymfocyty; myši inbrední C57BL; Stem Cells; Lymphopoiesis; T-Lymphocytes; ubikvitin; zvířata; kmenové buňky; Mice; Ubiquitin; myši transgenní; Mice, Inbred C57BL; Green Fluorescent Proteins; zelené fluorescenční proteiny; Animals